Combination therapy with thrombolysis - Yuluğ, Burak; Schaebitz, Wolf-Ruediger (Springer International Publishing AG, 2017)
Thrombolysis is the most effective treatment for acute ischemic stroke representing the basic therapeutic standard in the western world. Novel drug treatments are therefore unlikely to be developed as stand-alone approaches and every novel treatment should be considered as combination treatment together with thrombolysis. Such a combination should exert synergistic actions together with t-PA, and probably even more important decrease the potential adverse effects of thrombolysis including reperfusion-related adverse effects such as cytotoxin and free radical release and toxicity as well as BBB degradation and subsequent hemorrhagic complications. Preclinical data show that this approach can make thrombolysis safer and buy time for later treatment initiation. At current, the clinical evidence for this approach is relatively weak, but a systematic translation of preclinical findings into the human situation is ongoing with some recent hopeful examples from clinical trials.
Keywords: Neuroprotection; Acute Ischemic Stroke; Tissue Plasminogen Activator